The Karyotype report for some Ranunculus L. taxa growing in Turkey - Kursat, Murat; Gedik, Osman; Emre, Irfan (Univ Tokyo Cytologia, 2023)
The goal of this study is to conduct a thorough karyotypic examination of nine Ranunculus species pus, R. polyanthemos, R. repens, R. sericeus, R. sphaerospermus, and R. strigillosus] growing in Turkey. This study discovered that the basic number of Ranunculus taxa investigated was x=7 or 8. R. sphaerospermus and R. strigillosus have median and submedian chromosomes while other taxa have subterminal (st) chromosomes as well median (m) and submedian (sm). This investigation also revealed that R. kotschyi (B1), R. kotschyi (B2), and R. macrorrhynchus subsp. trigonocarpus are hexaploid, whereas R. repens and R. sphaerospermus are tetraploid. various karyotype asymmetry values, and the A1 and A2 in each taxon were also determined in this study. The Stebbins classification of R. brachylobus subsp. incisilobatus, R. polyanthemos, and R. repens were 3A while the other six taxa have 3B.
Keywords: Chromosome number; Karyotype; Polyploidy; Ranunculus; Stebbins classification